Early hominin paleoecology - Sponheimer, Matt (University Press of Colorado, 2013)
An introduction to the multidisciplinary field of hominin paleoecology for advanced undergraduate students and beginning graduate students, Early Hominin Paleoecology offers an up?to?date review of the relevant literature, exploring new research and synthesizing old and new ideas. Recent advances in the field and the laboratory are not only improving our understanding of human evolution but are also transforming it. Given the increasing specialization of the individual fields of study in hominin paleontology, communicating research results and data is difficult, especially to a broad audienc.